2021
DOI: 10.1101/2021.08.03.454908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The control and training of single motor units in isometric tasks are constrained by a common synaptic input signal

Abstract: Recent developments in neural interfaces enable the real-time and non-invasive tracking of motor neuron spiking activity. Such novel interfaces provide a promising basis for human motor augmentation by extracting potential high-dimensional control signals directly from the human nervous system. However, it is unclear how flexibly humans can control the activity of individual motor neurones to effectively increase the number of degrees-of-freedom available to coordinate multiple effectors simultaneously. Here, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our findings are potentially consistent with the observation that recruitment can be altered using biofeedback training in humans 47,5861,112 . An open question has been whether subjects learn to exploit the fact that rigid control embodies (fixed) exceptions to pure size-based recruitment 46,62 , or whether subjects gain direct voluntary control over previously unknown degrees of freedom. Our results indicate the latter is possible but don’t directly address this question; the prevalence of flexibility during voluntary movement doesn’t necessarily imply it can be controlled under biofeedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are potentially consistent with the observation that recruitment can be altered using biofeedback training in humans 47,5861,112 . An open question has been whether subjects learn to exploit the fact that rigid control embodies (fixed) exceptions to pure size-based recruitment 46,62 , or whether subjects gain direct voluntary control over previously unknown degrees of freedom. Our results indicate the latter is possible but don’t directly address this question; the prevalence of flexibility during voluntary movement doesn’t necessarily imply it can be controlled under biofeedback.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that latent flexibility may be revealed via biofeedback training 46,47,5861 . However, it remains unclear whether subjects truly display flexible control or simply leverage known size-principle exceptions; biofeedback-based control appears quite limited 62 . Thomas 46 found biofeedback-based flexibility only in muscles with multiple actions and argued it is a trivial consequence of subjects learning to move differently (e.g., supinating versus flexing).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effect of independent inputs on force modulation is negligible because force modulation is mainly influenced by the common synaptic input received by a population of motor neurons (Farina & Negro, 2015;Farina et al, 2016). Accordingly, Bräcklein et al (2022) observed that it is very challenging for humans to voluntarily disrupt the common input to motor neurons innervating a single muscle and thus to achieve independent control. There is a greater likelihood that movement is controlled via common inputs to groups of motor neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Scientifically, a viable research platform, such as sEMG-RD, could enable studying, for example, the effects of neurofeedback on motor unit activity for novel human-machine interactions (Formento, Botros, and Carmena 2021;Bräcklein et al 2022Bräcklein et al , 2021, decoding of motor function (Stachaczyk et al 2020;Tanzarella et al 2023), or investigating the underpinning mechanisms of motor unit control (Marshall et al 2022;Hug et al 2023).…”
Section: Future Directionsmentioning
confidence: 99%